2022
DOI: 10.3389/fimmu.2022.994828
|View full text |Cite
|
Sign up to set email alerts
|

Pan-cancer analysis identifies migrasome-related genes as a potential immunotherapeutic target: A bulk omics research and single cell sequencing validation

Abstract: IntroductionThe migrasome is a newly discovered organelle that resembles extracellular vesicles in structure. However, the function of the migrasome in tumors, particularly in relation to tumor immunity and tumor microenvironment, is unclear.MethodsGene expression data, copy number variation raw data, and methylation data of 33 cancer types were downloaded from The Cancer Genome Atlas database. Immunohistochemistry (IHC) based on 114 case of colorectal cancer was used to validate the expression of the migrasom… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
20
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 17 publications
(20 citation statements)
references
References 37 publications
0
20
0
Order By: Relevance
“…IL1B can also enhance the signal transduction of CTLA4, and targeting the IL1B-CTLA4 axis can effectively inhibit the occurrence of metastatic and recurrent colon cancer (69). ITGA5 is a crucial immunotherapy predictive target that is thought to be crucial in the incidence and progression of many cancers (70)(71)(72). CST7 is associated with activation of CD4T and CD8T cells in liver cancer (73).…”
Section: Discussionmentioning
confidence: 99%
“…IL1B can also enhance the signal transduction of CTLA4, and targeting the IL1B-CTLA4 axis can effectively inhibit the occurrence of metastatic and recurrent colon cancer (69). ITGA5 is a crucial immunotherapy predictive target that is thought to be crucial in the incidence and progression of many cancers (70)(71)(72). CST7 is associated with activation of CD4T and CD8T cells in liver cancer (73).…”
Section: Discussionmentioning
confidence: 99%
“…In a recent study, Qin and his group used the TIDE, showing that enhanced TIDE scores correlate to a higher expression of migrasomes—a novel, identified, large vesicle containing chemokines, cytokines, and growth factors able to promote tumor metastasis and immune escape, reducing the response to ICI. Additionally, the researchers also evaluated ESTIMATE scores of migrasomes in different tumors, finding out that patients treated with immunotherapy had higher scores, which correlates with a better prognosis [ 18 ].…”
Section: Dissecting the Tme With Multi-omics Approachmentioning
confidence: 99%
“…Furthermore, an exploratory analysis using RNA seq observed a correlation between the T-cell-inflamed gene expression profile (TcellinfGEP) with the Objective Response Rate (ORR) and Progression-Free Survival (PFS), specifically for pembrolizumab. The UMIN000025947 study (phase I/II) investigated a combined treatment (nivolumab, paclitaxel, and ramucirumab) used after the first line along with a phase II trial held by the Arbeitsgemeinschaft Internistische Onkologie (AIO), highlighting the CPS’s prognostic value in predicting the ICI response [ 18 ]. Similarly, the MAHOGANY study explored the combination of margetuximab (anti-HER2) and pembrolizumab (anti-PD-1), confirming the role of CPS as a predictive score [ 48 ].…”
Section: In-depth Cancer-type Analysis: Focus On Clinical Trialsmentioning
confidence: 99%
“…TSPAN4 is abundant in the migrasome membrane and is one of the most effective tetraspanins for migrasome induction [46], stabilizing the migrasome structure and acting as a migrasome marker [6,60]. The expressionof APPROVED GALLEY PROOF migrasome-related genes such as pigk, itgb1, and tspan4 are significantly up-regulated in a variety of tumor types [61][62][63]. Moreover, expression levels of multiple migrasome-related genes were associated with a poorer prognosis and drug sensitivity [61].…”
Section: Migrasomes In Diseasesmentioning
confidence: 99%
“…The expressionof APPROVED GALLEY PROOF migrasome-related genes such as pigk, itgb1, and tspan4 are significantly up-regulated in a variety of tumor types [61][62][63]. Moreover, expression levels of multiple migrasome-related genes were associated with a poorer prognosis and drug sensitivity [61]. Using single-cell sequencing analysis, Yue Zheng et al showed that the migrasome-related gene tspan4 was highly correlated with the atherosclerosis regression-associated macrophages, intraplaque hemorrhage, and ruptured plaques [62].…”
Section: Migrasomes In Diseasesmentioning
confidence: 99%